Lemon Dietary Fibre-Based Powder as a Promising Ingredient for the Food Industry: Enhancing Mortadella Nutritional Quality - Daniela Magalhães; Cristina V. Rodrigues; Carmen Botella-Martinez; Nuria Muñoz-Tebar; José Angel Pérez-Álvarez; Manuel Viuda-Martos; Paula Teixeira; Manuela Pintado (Foods)
Lemon co-products are valuable due to their high dietary fibre, making them significant for valorisation. This research aimed to characterise an innovative lemon dietary fibre (LDF) obtained through integrated extraction (of essential oil, phenolic compounds (PCs), and pectin) by evaluating its chemical, physicochemical, structural, techno-functional, total phenolic content, and antioxidant and antibacterial properties. The effects of incorporating LDF (3% and 6%) into mortadella, a bologna-type sausage, on chemical, physicochemical, technological, and sensory properties were analysed. LDF exhibited a total dietary fibre content of 85.79%, mainly insoluble (52.55%). Hesperidin (89.97–894.44 mg/100 g DW) and eriocitrin (68.75–146.35 mg/100 g DW) were the major free PCs. The major bound PCs were vanillin (5.90–9.16 mg/100 g DW) and apigenin-7-O-glucoside (8.82 mg/100 g DW). This functional ingredient demonstrated antioxidant and antibacterial activity. LDF significantly influenced mortadella’s colour, texture, and mineral composition. Higher levels of LDF result in a paler colour and increased hardness and contribute to reducing sodium levels of the final product. It also decreased residual nitrite levels, although this reduction was followed by a slight increase in lipid oxidation, which remained below the rancidity threshold (≥1.0), ensuring acceptable product quality. Sensory evaluation revealed positive feedback, favouring the 3% LDF formulation.